Gene polymorphism of cytochrome P450 significantly affects lung cancer susceptibility. (1st July 2019) - Li, Meng; Li, Anqi; He, Ruiqing; Dang, Wenhui; Liu, Xinyu; Yang, Tian; Shi, Puyu; Bu, Xiang; Gao, Dan; Zhang, Ning; Du, Shuli; Jin, Tianbo; et al.
Abstract: Background: Cytochrome P450 (CYPs) are heme proteins involved in the metabolism of a variety of endogenous and exogenous substances and play an important role in the carcinogenesis mechanisms of environmental and hereditary factors. The objective of this study was to investigate how polymorphisms of CYPs correlate with lung cancer (LC) susceptibility. Methods: Six single nucleotide polymorphisms (SNPs) were genotyped in this study. The chi‐square test and unconditional logistic regression model were used to evaluate the correlation between SNPs and LC susceptibility. The expressions and survival data of genes in patients with LC were mined using Oncomine and Kaplan‐Meier Plotter database. Results: Four SNPs were found to be significantly associated with the risk of LC development ( P  < 0.05). The most significant correlation was that the A allele and AA genotype of CYP2D6 rs1065852 were associated with increased risk of LC development (adjusted odds ratio [OR] = 1.35, 95% confidence interval [95%CI] = 1.13‐1.60, P  = 9.04e‐4; OR = 1.83, 95%CI = 1.29‐2.59, P  = 0.001 respectively). Similar association of this variant was also found in the subgroups of male patients, cases in III‐IV stages, positive lymph node, squamous cell carcinomas and adenocarcinomas. Whereas rs1065852 was considered as protective factor in females (adjusted OR = 0.33, 95% CI = 0.16‐0.70, P  = 0.004). In stratified analyses, the association of CYP24A1 rs2762934, CYP24A1 rs6068816, CYP20A1 rs2043449 polymorphism with LC risk appeared stronger in some subgroups. CYP2D6, CYP24A1 and CYP20A 1 are overexpressed in some pathological types of LC ( P  < 0.05), and high levels of CYP2D6 and CYP20A1 indicate poor and good prognosis of LC, respectively. Conclusion: This study revealed that rs1065852, rs2043449, rs2762s934, and rs6068816 of CYPs were associated with LC susceptibility in the Northwestern Chinese Han population; CYP2D6 and CYP20A 1 were overexpressed and correlated with prognosis of LC. Abstract : Our study reports first a possible association between the SNPs CYP2D6 rs1065852, CYP20A1 rs2043449, CYP24A1 rs2762934, CYP24A1 rs6068816 and lung cancer risk in the Northwestern Chinese Han population. In addition, we explored the overexpression of candidate genes in lung cancer and estimated the relationship between lung cancer prognosis and genes expression level in survival analysis using Oncomine and Kaplan‐Meier Plotter database, which could potentially contribute to elucidate the etiology of lung cancer and be used as diagnostic and prognostic molecular markers for lung cancer in Northwest Chinese Han population.